Risk of Respiratory Tract Infection Transmission in The Hajj Organizing Committee at the Surabaya Pilgrimage Quarantine - Umah, Isna Rohmatul; Indradmojo, Christyaji (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v3i0.3682, 2026)
Acute Respiratory Tract Infections (RTIs) are among the most common illnesses occurring during the Hajj pilgrimage, particularly in crowded environments such as during the debarkation phase. Transmission occurs through droplets or airborne and can affect not only pilgrims but also Hajj organizing committee members (PPIH) who interact directly with them. The risk of infection is high due to close contact, high population density, and inconsistent use of personal protective equipment. This study aims to describe the occurrence of RTIs among PPIH members at the Surabaya Debarkation and identify preventive measures to minimize the risk of transmission. This descriptive observational case study involved hajj organizing committee members who presented with respiratory complaints at the Hajj Dormitory Clinic in Sukolilo, Surabaya, during June 12–July 12, 2025. Examinations included temperature measurement using a thermogun, assessment of vital signs, and interviews regarding respiratory symptoms such as cough, cold, and fever. A total of 20 respondents were reported with RTI symptoms, most of whom were aged 30–40 years (45%) and worked in logistics (30%) or reception (25%). Most respondents experienced symptoms for 1–2 days (50%), indicating mild and self-limiting infections. The main risk factors for RTIs transmission among committee include overcrowding, poor ventilation, and direct contact without adequate protection. Preventive measures should include complete vaccination (influenza, COVID-19, and pneumococcal for high-risk individuals), proper personal protective equipment use (medical/N95 masks, gloves, face shields), hand hygiene, cough etiquette, regular disinfection, and health screening before and after duty.